Information technology-based environmental management: A review - Valdez, Rogelio Estalin Ureta; Orozco, Ángel Patricio Flores; Pérez, Luis Patricio Tierra; Zambrano, Patricio Vladimir Méndez (International Journal of Innovative Research and Scientific Studies, 2024)
This study aimed to describe the role of information and communication technologies (ICT) in the management of natural resources. We conducted a systematic review of 320 articles from academic databases like Scopus, Latindex, Scielo, Dialnet, Redalyc, and Google, scanning the period from 2018 to 2023. We selected forty articles that discussed the application of ICT in predicting and mitigating issues related to climate change, erosion, environmental pollution, drought, and floods. The results indicated that climate change is one of the main drivers of environmental problems such as droughts and floods. Therefore, we concentrated our efforts on developing technologies like artificial intelligence (AI), machine learning (ML), the use of sensors, the Internet, and others. These tools make it possible to manage large amounts of information in real time and make informed decisions to prevent the aforementioned environmental problems. Despite the success of new technologies, it is important to note that they are not within the reach of the entire population due to the existing gap between the most technologically developed countries and those that are lagging. Therefore, we need to make additional efforts to enhance accessibility to technologies, enabling all countries to reap their benefits. In addition, efficient management of natural resources is required to minimize soil and water pollution. This implies the adoption of sustainable practices in the productive sector.